Increased serum p53 antibody levels indicate poor prognosis in patients with colorectal cancer. - Kressner, U. (Nature Publishing Group, 1998)
Serum p53 antibody levels were analysed using an enzyme-linked immunosorbent assay in serum samples obtained before surgery from 184 consecutive patients with primary colorectal cancer. Possible associations with tumour stage and tumour differentiation and the relation to patient survival time after a median follow-up of 6 years were studied. Analysis of serum p53 antibodies in the entire material demonstrated prognostic value in univariate analysis (P = 0.02); a finding that did not remain (P = 0.07) when the Dukes' stage was included in a multivariate analysis model. When the survival analysis was restricted to the potentially cured patients in Dukes' stages A-C, the serum p53 antibody levels retained independent prognostic value (P = 0.03). No clear association with tumour differentiation was found. We conclude that analysis of serum p53 antibodies may be of value for the identification of patients with different prognoses. This may be of relevance for selection of patients for adjuvant treatment.